Negative pressure wound therapy in surgical wounds: a prospective comparative study - S., Chandrashekar; V., Veena (International Surgery Journal, 2017)
Background: The goal of treating any type of wound is to promote healing in a timely fashion. Wound healing is most successful in moist, clean and warm environment. One of the most significant discoveries in wound management is the improvement of wounds with negative pressure wound therapy (NPWT). NPWT entails applying topical negative pressure to a wound. In this study, the efficacy of topical negative pressure dressing was assessed in comparison with a control group using conventional moist wound dressings in wound healing. Methods: This is a prospective comparative study conducted on 50 patients with acute, sub-acute and chronic open wounds of various aetiologies. The patients were divided into two groups each group comprising of 25 patients. One group received negative pressure wound dressing while the other group received conventional saline moistened gauze dressing. Wounds were assessed depending on wound size, appearance of granulation tissue, wound bed score, reduction in wound size along with the time taken for wound closure. Statistical analysis was done using unpaired T-test and paired T-test. A p value of <0.05 was taken as significant. Results: Present study showed that there was a statistically significant decrease in the wound size in study group, early appearance of granulation tissue, significant increase in the wound score and faster rate of wound closure compared to the control group. Conclusions: Negative pressure wound therapy can be considered as a superior option in the management of open wounds.